2017
DOI: 10.1186/s12889-017-4963-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing a policy game intervention to enhance collaboration in public health policymaking in three European countries

Abstract: BackgroundOne of the key elements to enhance the uptake of evidence in public health policies is stimulating cross-sector collaboration. An intervention stimulating collaboration is a policy game. The aim of this study was to describe the design and methods of the development process of the policy game ‘In2Action’ within a real-life setting of public health policymaking networks in the Netherlands, Denmark and Romania.MethodsThe development of the policy game intervention consisted of three phases, pre interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…11,12 Five articles discuss school health policy, prevention and regulation of internet game disorder, public policy evaluation and literature review of video game addiction policy responses, policymaking interventions and policy strategies for substance abuse in adolescents. [13][14][15][16][17] One article on the analysis of the Juvenile Contraception Law, 18 one article on the literature review on the prevention of mental health disorders. 19 One article systematically reviewed health promotion interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Five articles discuss school health policy, prevention and regulation of internet game disorder, public policy evaluation and literature review of video game addiction policy responses, policymaking interventions and policy strategies for substance abuse in adolescents. [13][14][15][16][17] One article on the analysis of the Juvenile Contraception Law, 18 one article on the literature review on the prevention of mental health disorders. 19 One article systematically reviewed health promotion interventions.…”
Section: Resultsmentioning
confidence: 99%
“…7 An innovative intervention design has been developed in three European countries for public health policymaking, focusing on collaboration within policymaking networks. 16 Lillefjell and Mass research, 2022 examines multi-sector involvement and collaboration in implementing health promotion principles at the local level. 11 The level of participation and support of Hepatitis C policy-making in Iran was investigated, the conclusion of the study indicated that involvement in Hepatitis C Virus related stakeholder policy-making is generally low and has implications for policymakers and decisions regarding the The analysis presented shows that the Drink Free Days (DFD) campaign is not used explicitly by the industry for public relations purposes.…”
Section: Resultsmentioning
confidence: 99%
“…6 In the past decade, health policy debate simulations have modelled global, 7 international/regional, 8 national 9 and local policymaking bodies. 10 These addressed pertinent ethical, cultural and environmental issues in health, such as international maternal surrogacy legislation, 7 ‘Health in All Policies’, 10 the Affordable Care Act 11 and even the health impacts of climate change, as recently published in The Lancet Planetary Health . 8 The appearance of multiplayer simulations on digital platforms, such as the ‘Online Model United Nations’ (O-MUN), 12 places these policymaking simulations within the discourse on ‘serious games’.…”
Section: Online Health Policy Debate Simulations As ‘Serious Games’mentioning
confidence: 99%
“…The interest in integrating public health with other policy domains has increased over the years with programs such as Health in All Policies and the Whole-of-Government approach [ 4 ]. Based on studies that examined such programs, cross-sector collaboration was found to be of major importance when integrating public health with other sectors [ 5 , 6 ]. However, cross-sector collaboration is also found to be a challenge due to stakeholders having different perspectives, norms, and values [ 4 , 7 , 8 ], especially when integrating the domains of health and the physical environment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%